The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1073/pnas.93.18.9431
|View full text |Cite
|
Sign up to set email alerts
|

The mode of action and the structure of a herbicide in complex with its target: binding of activated hydantocidin to the feedback regulation site of adenylosuccinate synthetase.

Abstract: (+)-Hydantocidin, a recently discovered natural spironucleoside with potent herbicidal activity, is shown to be a proherbicide that, after phosphorylation at the 5' position, inhibits adenylosuccinate synthetase, an enzyme involved in de novo purine synthesis. The mode of binding of hydantocidin 5'-monophosphate to the target enzyme was analyzed by determining the crystal structure of the enzyme-inhibitor complex at 2.6-A resolution. It was found that adenylosuccinate synthetase binds the phosphorylated compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 42 publications
(38 reference statements)
1
35
0
Order By: Relevance
“…The structure was solved by molecular replacement with the program AmoRe (27). The initial model was the E. coli synthetase (Protein Data Bank identifier 1SON) (18). Model building and refinement employed the programs XTALVIEW (28) and CNS (29), respectively.…”
mentioning
confidence: 99%
“…The structure was solved by molecular replacement with the program AmoRe (27). The initial model was the E. coli synthetase (Protein Data Bank identifier 1SON) (18). Model building and refinement employed the programs XTALVIEW (28) and CNS (29), respectively.…”
mentioning
confidence: 99%
“…Hydantocidin was shown to be a proherbicide that, after phosphorylation at the 5' position, inhibits adenylosuccinate synthase (Fonné-Pfister et al, 1996). The mode of binding of hydantocidin 5'-monophosphate (HMP) to the target enzyme from E. coli was analyzed by determining the crystal structure of the enzyme inhibitor complex.…”
Section: Research For Finding New Target Sitesmentioning
confidence: 99%
“…Hydantocidin, known as pro-herbicide, is first converted into hydantocidin monophosphate (HMP), and this molecule mimics either IMP or AMP. Evidence from crystallographic studies of the enzyme showed that hydantocidin replaced IMP in the active site [7][8][9][10] . Hadacidin is also a natural substrate of AdSS, which was reported as a competitive inhibitor of aspartic acid but affecting the enzyme at a different site 11 .…”
Section: Adenylosuccinate Synthasementioning
confidence: 99%